Determining the priority of university technology transfer office activities for each group of the stakeholder using SWARA method - Karadayı, Melis Almula; Ekinci, Yeliz (Springer, 2022)
This chapter is an attempt to summarize the University Technology Transfer Office (UTTO) activities firstly. The main objective is to determine the priority of these activities for each group of the stakeholder; namely, students, academicians, and industry. UTTOs promote the conversion of knowledge created at university to marketable goods; which makes them crucial for the countries. Moreover, UTTOs serve to the economic development of countries by bringing companies and researchers together and motivating them for technology transfer. In this study, we firstly examine the UTTOs to understand the dynamics of these offices. Then, we list the critical activities of the UTTOs and conduct three surveys specific to each group of the stakeholder where the participants evaluate the relative importance of the activities determined. Importance/priority of UTTO activities is determined using Stepwise Weight Assessment Ratio Analysis (SWARA) method, for each group of the stakeholder. Finally, the results are presented, which will shed light on the decisions in managing and organizing UTTO activities.
Keywords: Multiple-Criteria Decision-Making; Stepwise Weight Assessment Ratio Analysis (SWARA); Technology Transfer; University Technology Transfer Offices